Variation in “foramina transversaria” of human cervical vertebrae in the medieval population from Sypniewo (Poland) - Kwiatkowska, Barbara; Szczurowski, Jacek; Nowakowski, Dariusz (Anthropological Review, 2014)
Since the foramina provide important reference points to radiologists and surgeons, and because their shape and size may affect the blood supply to the cerebellum and the brainstem, the knowledge of the variation of foramina transversaria is essential from the medical point of view. The variation in the number, size and shape of foramina transversaria was studied based on 129 skeletons (68 male, 61 female, total of 1065 foramina) from the environs of Sypniewo. In both sexes single foramina were the most frequent (ca. 70%); in females no double foramina were observed, while triple foramina appeared only twice. In males double foramina formed ca. 40% and triple foramina were very rare. The shape and size of foramina depended to the same extent on the position of the vertebra and on the body side.